Suitability Of Kappaphycus alvarezi Cultivation In Obi Island, North Maluku - Labenua, Rusmawati; Aris, Muhammad (Sam Ratulangi University, 2021)
The potential of aquaculture in this area, especially the Obi Islands, has not been fully utilized. One of the commodities that can be developed is Kappaphycus alvarezii seaweed. This commodity is the main commodity for aquaculture which has important economic value. Analysis of the suitability of waters for seaweed cultivation is an early stage of activity that will determine the success of Kappaphycus alvarezii cultivation. Therefore, this study aims to assess the suitability of the waters for the development of Kappaphycus alvarezii seaweed cultivation on the island of Obi. This research was conducted in the waters of Akegula Village, Kampung Baru, and Kawasi, South Halmahera Regency, North Maluku Province, Indonesia. There are 3 stations in Akegula waters, 3 stations in waters in Kampung Baru waters, 4 stations in Kawasi waters, and 3 stations in Soligi waters. Water quality parameters observed were temperature, brightness, depth, current velocity, salinity, pH, dissolved oxygen, nitrate, and phosphate. The results showed that the waters of Akegula, Kampung Baru, Kawasi, and Soligi were very suitable.Keywords: Kappaphycus alvarezii; Water quality; Obi IslandAbstrakPotensi perikanan budidaya di kawasan ini khususnya kepulauan Obi, belum dimanfaatkan secara maksimal. Salah satu komoditas yang dapat dikembangkan adalah rumput laut Kappaphycus alvarezii. Komoditas ini merupakan komoditas utama budidaya perikanan yang bernilai ekonomis penting. Analisa kesesuaian perairan untuk budidaya rumput laut merupakan tahapan awal keigatan yang sangat menentukan keberhasilan budidaya Kappaphycus alvarezii. Oleh karena itu, penelitian ini bertujuan untuk mengkaji kesesuaian perairan untuk pengembangan budidaya rumput laut Kappaphycus alvarezii di pulau Obi. Penelitian ini dilakukan di perairan Desa Akegula, Kampung Baru, dan Kawasi, Kabupaten Halmahera Selatan, Provinsi Maluku Utara, Indonesia. Terdapat 3 stasiun di perairan Akegula, 3 stasiun di perairan di perairan Kampung Baru, 4 stasiun di perairan Kawasi,Â dan 3 stasiun di perairan Soligi. Parameter kualitas air yang diamati adalah suhu, kecerahan, kedalaman, kecepatan arus, salinitas, pH, oksigen terlarut, nitrat dan fosfat. Hasil penelitian menunjukan bahwa perairan Akegula, Kampung Baru, Kawasi dan Soligi sangat sesuai.Kata Kunci: Kappaphycus alvarezii; Kualitas perairan; Analisa Kesesuaian; Pulau Obi